ANALYSIS OF STUDENTS DIFFICULTIES IN THE LEARNING PROJECT FOR STRENGTHENING THE PANCASILA STUDENT PROFILE OF THE MERDEKA CURRICULUM AT SMAN 8 PONTIANAK - Herliani, Herliani; Asriati, Nuraini; Adlika, Nur Meily (GEOREFERENCE, 2024)
This study aims to analyze various factors influencing students' learning challenges in the Pancasila Student Profile Strengthening Project within the implementation of an independent curriculum at SMAN 8 Pontianak. Employing a qualitative field approach akin to previous research, the study includes 7 tenth-grade students, Subject Teachers, and the Curriculum Deputy as participants. Data collection techniques involve passive participant observation and direct communication methods, utilizing observation and interview instruments. Research implementation utilizes non-participant observation techniques. Findings suggest that learning difficulties in the Project within the independent curriculum implementation among students are influenced by factors such as students' health conditions, study habits, learning interests, as well as family, peer, and school environments. The conclusion drawn is that internal factors like project learning interest, health conditions, and attitudes towards project-based learning seem more dominant than external factors in causing learning challenges in this context. However, it's important to note that internal and external factors can interact and influence each other, underscoring the need for a holistic approach to addressing learning difficulties.